PENGARUH PERTUMBUHAN PERUSAHAAN, UKURAN PERUSAHAAN, PROFITABILITAS, DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR TAHUN 2015 – 2017 (Studi pada perusahaan manufaktur yang terdaftar di BEI 2015 - 2017) - Lie, Steven Gunawan, 15.05.52.0171; Srimindarti,, Ceacilia (Students' Journal of Accounting and Banking, 2019)
This study aims to examine the effect of company growth, firm size, and profitability on firm value with a legal structure as an intervening variable. This research was conducted in Indonesia by using an analysis unit of manufacturing companies that have been listed on the Indonesia Stock Exchange. The sampling method uses purposive sampling with a research period of 2015 to 2017 and obtained as many as 185 companies. The data analysis technique used is multiple linear regression analysis. The results of the study show that company growth, company size, and profitability influence the capital structure. Company growth, company size, and profitability influence the value of the company. Capital structure has no significant negative effect on firm value. Mediation testing of capital structure shows that capital structure cannot mediate the relationship of company growth, company size, and profitability to firm value.